(untitled) (Indian Journal of Arid Horticulture, 2025)
Onion (Allium cepa L.) stands among the most widely cultivated vegetable crops worldwide, valued for both its culinary uses and rich phytochemical composition and associated health benefits. Among the bioactive compounds, phenolics, flavonoids and anthocyanins play crucial roles in determining antioxidant capacity, nutritional quality and market preference. This review compiles recent findings on how environmental conditions and genotypes influence on onion quality traits. Evidence consistently demonstrates wide variability among cultivars, with red onions exhibiting the highest values of total phenolics, flavonoids, anthocyanins and antioxidants, followed by yellow and followed by white type cultivars. Antioxidant activity, assessed through diverse assays such as FRAP, DPPH showed variation across various parts of onion plant. Notably, onion skins, particularly from red varieties, contain substantially higher concentrations of flavonoids and anthocyanins than bulbs, showing their potential as valuable by-products. Environmental factors, including cultivation conditions, geographic location and harvest timing, further modulate phytochemical accumulation, highlighting the importance of genotype x environment interactions. Overall, the biochemical diversity observed across onion genotypes and ecotypes presents opportunities for breeding and selection strategies aimed at enhancing nutritional and functional quality, while also emphasizing the need for standardized analytical approaches.